Key role of atmospheric water content in the formation of regional haze in southern China. (1st November 2019) - Kong, Liuwei; Hu, Min; Tan, Qinwen; Feng, Miao; Qu, Yu; An, Junling; Zhang, Yuanhang; Liu, Xingang; Cheng, Nianliang; Deng, Yijun; Zhai, Ruixiao; Wang, Zheng
Abstract: To elucidate the formation mechanism of haze and the important role of atmospheric humidity in haze formation, comprehensive observations were carried out at regional sites in the Pearl River Delta region of southern China from October 22 to November 6, 2014. Meteorological parameters, chemical compositions, aerosol secondary conversions and aerosol radiative forcing were analyzed. A lower wind speed (WS) and planetary boundary layer (PBL) can inhibit the horizontal and vertical diffusion of pollutants, leading to the accumulation of pollutant concentrations. A higher atmospheric relative humidity (RH) can promote aerosol secondary conversions, leading to an increase in secondary aerosol concentrations. Aerosol scattering hygroscopic growth properties and aerosol single scattering albedo (SSA) also increase with increasing RH, resulting in an increase in aerosol radiative forcing and a decrease in the PBL height, aggravating the formation of meteorological conditions that are not conducive to the dilution of pollutants. Conversely, a higher aerosol concentration also increases aerosol radiative forcing, forming a positive feedback loop. When the RH decreases and the WS increases, the loop enters a negative feedback process to reduce pollutant concentration. Graphical abstract: Image 1 Highlights: Formation and evolution of haze in the PRD of South China were investigated. Sìondary conversion and hygroscopic growth of aerosols were analyzed. Higher atmospheric humidity increased aerosol radiative forcing, lowering PBL. Increased atmospheric humidity was the trigger for haze formation.